Antiphospholipid syndrome presenting with acute digital ischaemia, avascular necrosis of the femoral head and superior mesenteric artery thrombus. (20th November 2012) - Crome, Christopher Robert; Rajagopalan, Sriram; Kuhan, Ganesh; Fluck, Nicholas
Abstract : This case illustrates a rare and unique case of a 73-year-old woman who presents with a rapidly developing digital ischaemia, superior mesenteric artery thrombus with positive-lupus anticoagulant. She then developed avascular necrosis of the femoral head. Discussion of the process of diagnosis and management of antiphospholipid syndrome and catastrophic antiphospholipid syndrome are reported.